2005
DOI: 10.3168/jds.s0022-0302(05)73038-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dry Period Versus Continuous Lactation on Metabolic Status and Performance in Periparturient Cows

Abstract: It has been argued that dairy cows with a high genetic milk production potential can maintain high milk production even with total omission of the dry period. Further, when omitting the dry period, cows are believed to experience fewer metabolic changes during the transition from late gestation to early lactation compared with cows having a traditional dry period. The performance and metabolic response to omission of the dry period for cows with an expected peak milk yield higher than 45 kg/d were studied in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
120
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(146 citation statements)
references
References 34 publications
19
120
2
5
Order By: Relevance
“…Similar to fat and protein content, the lactose content was increased during the last 2 months of gestation in CM cows (Remond et al, 1997a). However, in another study, the weekly content of lactose was decreased from week 5 to week 0 prepartum (Andersen et al, 2005). In two studies by our laboratory, no change in lactose concentration of milk was detected during late gestation .…”
Section: Impact On Milk Yieldmentioning
confidence: 72%
See 4 more Smart Citations
“…Similar to fat and protein content, the lactose content was increased during the last 2 months of gestation in CM cows (Remond et al, 1997a). However, in another study, the weekly content of lactose was decreased from week 5 to week 0 prepartum (Andersen et al, 2005). In two studies by our laboratory, no change in lactose concentration of milk was detected during late gestation .…”
Section: Impact On Milk Yieldmentioning
confidence: 72%
“…Remond et al (1992 and1997a) claimed that the ratio of casein/total protein was decreased when milk yield was reduced during late gestation in CM cows (,6 kg/day). In another study, the weekly content of milk protein was reported to be increased from week 5 to immediately before parturition in cows with eliminated dry periods (Andersen et al, 2005). Milk protein content was increased during the entire late gestation in CM glands and it was maximal at 1 to 2 weeks before parturition .…”
Section: Impact On Milk Yieldmentioning
confidence: 89%
See 3 more Smart Citations